Pragmatic Skills in Typically Developing Infants - Shilpashri H.N.; Shyamala K. Chengappa (Journal of All India Institute of Speech and Hearing)
Communication refers to exchange of information between the speaker and listener. Among the various modes, language forms the primary means of human communication. The knowledge of language is viewed as an integration of content, form and its use. The use of language in social contexts refers to as pragmatics. Pragmatics forms a critical intersection for children’s developing language competence and social interactions. As speech and motor milestones develop, pragmatic skills also develop during infancy. The present study was an attempt to understand the type of pragmatic skills acquired at the age of 6 months to 12 months of infancy with Kannada as their mother tongue. Eight typically developing infants (4 male and 4 female) were considered for the present study. One hour audio - video sample of mother-child interaction was recorded and analyzed for eight different pragmatic skills. The results of the present study are discussed in terms of acquisition of pragmatic skills during infancy.